Effects of Bedding Material on Equine Lower Airway Inflammation: A Comparison of Two Peat Beddings, Wood Pellet, and Straw Pellet - Mönki, Jenni; Saastamoinen, Markku; Karikoski, Ninja; Norring, Marianna; Rajamäki, Minna; Mykkänen, Anna (Frontiers in Veterinary Science, 2021)
The effects of bedding material on air quality are important amongst horses worldwide. Respiratory diseases, especially equine asthma, are highly prevalent with air hygiene playing a major role on the pathophysiology of these diseases. The objective of our study was to investigate the effects of four bedding materials on the respiratory signs, tracheal mucus score, and tracheal wash (TW) and bronchoalveolar lavage fluid (BALF) cytology in healthy adult horses. The study design was a prospective controlled cross-over study, and the subjects were healthy adult riding school horses (n = 32) from a single stable. Wood pellet, straw pellet, and loosely stored peat (Peat 3) were compared to peat packed in plastic-covered bales (Peat 2). Lower airway endoscopy and sampling (TW and BALF) for cytological examination were performed after each 35-day bedding period. The tracheal mucus scores (P = 0.014) and respiratory rate (P = 0.026) were higher during the straw pellet period compared to the Peat 2 period. The respiratory rate was lower during the wood pellet period compared to the Peat 2 period (P = 0.004). The TW neutrophil percentage during the straw pellet period was higher compared to the Peat 2 period (P = 0.0003). The BALF neutrophil percentage was higher during the straw pellet period (P = 0.005) and during the Peat 3 period compared to the Peat 2 period (P = 0.04). We conclude that baled peat (Peat 2) caused lower neutrophil percentages in the airway samples compared to straw pellet and loosely stored peat (Peat 3). No difference was observed between Peat 2 and wood pellet. The information gained from this study may assist veterinarians and horse owners in selecting appropriate bedding materials, especially for horses with equine asthma.